Loading and Release Profile Assay of Carbonated Hydroxyapatite Incorporated with Propolis as Bone Graft Material - Indi Kusumawati; Suryono Suryono; Ahmad Syaify (Majalah Obat Tradisional, 2020)
Periodontitis can lead to the destruction of the alveolar bone. The loss of the alveolar bone can be treated using carbonated hydroxyapatite (CHA) as a bone graft material. However, CHA is an alloplastic graft whose primary function is to act as a scaffold, but it is unable to stimulate the process of bone regeneration. Carbonated hydroxyapatite is an avascular synthetic material, which will increase the risk of bacterial adhesion on site that can lead to unsuccessful periodontal therapy. The incorporation of propolis into CHA is expected to add antibacterial capability into CHA. Besides its antibacterial property, propolis also has a bone regenerating effect. Mixing CHA with propolis needs to consider the process of loading the active ingredients into the carrier. The release of propolis is expected to occur gradually over a lengthy period. The purpose of this study was to analyze the loading and releasing assay for propolis incorporated with CHA. A propolis solution of 5%, 7.5%, and 10% was each incorporated into 10 mg of CHA. The loading percentage and releasing assay of propolis were measured. The absorbance reading was done at 289 nm using a UV-vis. It was shown that a 10% propolis solution had the highest loading percentage (32.08%), while the 5% propolis solution had the smallest loading percentage (10.63%). The propolis releasing profiles in all concentration groups were similar. The difference in propolis concentration incorporated with CHA affected the loading percentage but did not affect the propolis releasing assay.